A circumpolar review of the breeding distribution and habitat use of the snow petrel (Pagodroma nivea), the world’s most southerly breeding vertebrate - Francis, Josie; Wakefield, Ewan; Jamieson, Stewart S. R.; Phillips, Richard A.; Hodgson, Dominic A.; Southwell, Colin; Emmerson, Louise; Fretwell, Peter; Bentley, Michael J.; McClymont, Erin L. (Polar biology, 2025)
Knowledge of the spatial distribution of many polar seabird species is incomplete due to the remoteness of their breeding locations. Here, we compiled a new database of published and unpublished records of all known snow petrel Pagodroma nivea breeding sites. We quantified local environmental conditions at sites by appending indices of climate and substrate, and regional-scale conditions by appending 30 year mean (1992–2021) sea-ice conditions within accessible foraging areas. Breeding snow petrels are reported at 456 sites across Antarctica and subantarctic islands. Although many counts are old or have large margins of error, population estimates available for 222 known sites totalled a minimum of ~ 77400 breeding pairs. However with so many missing data, the true breeding population will be much higher. Most sites are close to the coast (median = 1.15 km) and research stations (median = 26 km). Median distance to the November sea-ice edge (breeding season sea-ice maximum) is 430 km. Locally, most nests occur in cavities in high-grade metamorphic rocks. Minimum air temperatures occur at inland sites, and maxima at their northern breeding limit. Breeding location and cavity selection is likely determined by availability of suitable breeding substrate within sustainable distance of suitable foraging habitat. Within this range, nest sites may then be selected based on local conditions such as cavity size and aspect. Our database will allow formal analyses of habitat selection and provides a baseline against which to monitor future snow petrel distribution changes in response to climate change.